Effective Design, Development, and Evaluation of Video Tutorials for Electronic Medical Record Training - Randhawa, Gurprit K.; Shachak, Aviv; Courtney, Karen L.; Kushniruk, Andre (ACI Open, 2020)
Background Electronic medical record (EMR) use by primary care physicians (PCP) in the United States and Canada is suboptimal, especially for supporting chronic diseases like diabetes. PCPs need postimplementation training to achieve value-adding EMR use. Video tutorials demonstrate how to accomplish tasks using software. However, there is a dearth of research on the use of video tutorials for EMR training.Objective The purpose of the study was to design, develop, and evaluate video tutorials for training PCPs in using EMR advanced features for diabetes care. This study addressed three research questions related to PCP's views of video tutorials as an EMR training method/approach, barriers, and facilitators to applying the EMR video tutorials to PCPs' practice, and how the design of EMR video tutorials can be improved.Methods The overall research study employed a QUAN (qual) mixed methods approach with an embedded design. This article focuses on the qualitative phase of the mixed methods study. A series of four theory-informed and evidence-based video tutorials for diabetes care was developed with a physician champion. Qualitative data were collected at four time points: 1 month before (O1), immediately before (O2), 3 months after (O3), and 6 months (O4) after the intervention. Semistructured interviews with participants were held at O3 and O4. Qualitative data were analyzed using thematic analysis.Results In total, 14 PCPs from the overall study participated in interviews (78%). The thematic analysis of the qualitative data revealed seven themes, which fall into two main categories: (1) design and development of EMR video tutorials, and (2) adoption and use of EMR video tutorials.Conclusion PCPs liked the EMR video tutorials for diabetes care, and would like more EMR video tutorials on various topics and EMR use levels. The study offers a roadmap for health informatics professionals everywhere to develop EMR training videos that meet evidence-based design criteria. It also help to identify opportunities to improve the design, delivery, and adoption of EMR video tutorials for future training interventions.
Keywords: electronic health records; computer user training; physicians; primary care; meaningful use; video tutorials